Oscillatory behavior of second order nonlinear diﬀerential equations with a sublinear neutral term - Grace, Said R.; Graef, John R. (Mathematical Modelling and Analysis, 2018)
The authors establish some new criteria for the oscillation of solutions of second order nonlinear diﬀerential equations with a sublinear neutral term by reducing the equation to a linear one. Their results are illustrated with an example.